Development of Psychology Based on Online with Edward Personality Preference Schedule and High Level Indonesian Collective Intelligence Test - Richard Juan putra Sudarto; Erdhi Widyarto Nugroho; Hendra Prasetya (Soegijapranata Catholic University, 2021)
Online psychotic are developed to keep up with current technological advancements. Application of Psychotest Development Based on Online with Edward Personality Preference Schedule and High-level Indonesian Collective Intelligence Test, developed for the benefit of the Soegijapranata Center for Applied Psychology. Making the application